El predominio del jacobinismo como una de las causas del fracaso en la construcción republicana - Ponce Pérez, Víctor Andrés (2021)
In the following work it is argued that the failure in the construction of the Republic, the absence of solid republican institutions, the lack of a system of political parties and the predominance of military and civil caudillismo has one of its explanations in the predominance of a Jacobin political philosophy from Independence to the present day. The study of Jacobinism is formulated from its metaphysical rationalist position that considers that reason is the only instrument to design societies and denies any importance to the existing institutions, history and traditions of a society. From this point of view, it is understood that, since the independence of the metropolis, the beginning of the Republic became the “foundation of a new era” without any connection with the institutions, history and traditions of Virreinato. In this context, neither liberals nor conservatives had institutions to defend or reform. The present investigation is formulated from a point of view of political philosophy and the philosophical hermeneutical method of political and historical texts is used. Likewise, the conclusions of this work are intended to be valid for the analysis of republican history and also for the current political situation of our days.